Effect of Climate Change on The Availability of River Water in The Village Kranji District Pekalongan - Karimah, Naelatul; Fianti, Fianti (Universitas Negeri Semarang, 2021)
Water is an important need in human life which is a natural resource which must be maintained availability. Changes in the land usage and weather can cause changes in the condition of water sources. These changes can affect the availability of water. Currently the river in Kranji Village, Kedungwuni Timur District, Pekalongan Regency, has decreased in quantity. If efforts to protect and repair the springs are not carried out, it can lead to the lost of water source. To better understand the problem of water availability in Kranji Village, East Kedungwuni District, Pekalongan Regency, it is necessary to conduct research that aims to determine the condition of water availability. The research was conducted by collecting data and information that can be used in the analysis of water availability. The data obtained in the form of secondary data, namely data from BMKG. The data were then be analyzed with the influence of climate change. The results showed that the rainfall in the Kranji Village area from 2011-2016 experienced fluctuations in regional rainfall. In 2017-2020 the rainfall rate in the region decreased to 91.8 mm. Design rainfall data in the Kranji Village area from 2011-2020 has an average Log X of 1.972. The amount of surface water has increased to 19% in the 10th year, reached 28.5% in the 15th year and reached 39% in the 20th year which were generated from the 2011-2020 study. Due to climate change, the mainstay flood discharge from runoff is estimated to decrease drastically, as well as rainwater that will seep into groundwater.